PENGGUNAAN ZAT PENGATUR TUMBUH SITOKININ DAN EKSTRAK BAHAN ORGANIK TERHADAP PERTUMBUHAN ANGGREK DENDROBIUM SECARA In-Vitro - Bryan Mokoginta; Beatrix Doodoh; Doortje. M. F. Sumampow (Universitas Sam Ratulangi, 2020)
ABSTRAKDendrobium orchids are one of the favorite orchid genera for orchid lovers. This is becausethis orchid is able to adapt to various growing environmental conditions. The growth media in tissueculture has a very big influence on the growth and development of the explants and the seeds itproduces. Cytokinins that play a role in stimulating cell division and inducing shoot formation. Someextracts of organic materials that are often used in plant tissue culture are extracts of tomatoes, corn,bananas and coconut water. This study aims to determine the best results of using cytokinins andextracts of organic matter and coconut water for in-vitro growth of Dendrobium orchids. This researchis a library research, which is a series of studies that are concerned with the method of collectinglibrary data, or research where the object of research is explored through various library information(books, encyclopedias, scientific journals and documents). The data used in this research is secondarydata. The data collection method used in this research is the documentation method. . The data analysisused in this study was annotated bibliography analysis.Based on research conducted in the form of literature searches, it can be concluded that byusing growth regulators cytokinins (in this case BAP) and extracts of organic matter, banana extract,tomato extract, corn extract and coconut water, it turns out that the best results are obtained with theuse of growth regulators Cytokinins ( namely BAP) 3 ppm with tomato extract organic matter.Kata Kunci: Zat Pengatur Tumbuh, Bahan Organik, Anggrek Dendrobium